Best Fitting Methods for The Mud Profile Equations - A Perwira Mulia Tarigan; Hasanul Arifin Purba (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2020)
In order to understand the dynamics of shoreline changes due to natural and anthropogenic causes, it is imperative for a coastal manager to comprehend the shore profile characteristics which are dependent on the sediment-wave interaction and can be depicted in a profile equation. Moreover, it is possible to derive the power form for the profile equation of a sandy coast based on the argument of wave energy dissipation per unit bed area and unit time. By using this same argument and considering the phenomenon that the main cause of wave damping over a muddy coast is due to energy absorption by the soft mud bottom, the mud profile equation can also be formulated. The aim of this study was to observe the mud profile equation geometry using best fitting method and to compare the characteristic features of the mud profiles using the field observation data. Shore profile data were measured from the muddy coast of Pantai Cermin in the eastern coast of North Sumatera Province. The data obtained were fitted to both the sand and mud profile equations. The procedures and results of the two best fitting methods, the nonlinear regression and the least square based trial and error search, were exhibited and compared. Several noteworthy features of the mud profile equation were found to be the same with the sand profile equation in describing the profile data. In order to provide a better profile and shoreline stabilization, it is recommended to use more complete observation data and good knowledge of shore profile by the coastal manager.